Composition Analysis of Airborne Microbiota in Outdoor and Indoor Based on Dust Separated by Micro-sized and Nano-sized - Jinho Yang; Ji-Hoon Seo; Young-Koo Jee; Yoon-Keun Kim; Jong-Ryeul Sohn (Aerosol and Air Quality Research)
Abstract Airborne microorganisms are associated with human health and awareness of the important influence of nano-sized extracellular vesicles (EVs) on health has risen. Thus, we analyzed the micro-sized microbes (m-MBs) and nano-sized microbial EVs (n-MEVs) of outdoor and indoor air through a field study in Seoul, Korea. We conducted 16S rDNA-based metagenomic analysis of m-MBs and n-MEVs in outdoor airborne dust (OAD), indoor airborne dust (IAD), and indoor dust from carpets (IDC). The dominant taxa in OAD were altered depending upon the outside environment, such as sunny, haze, and rainy. Also, dominant taxa in IAD and IDC were changed depending on the outside environment. In addition, there were differences of microbiome composition and diversity between the m-MB and n-MEV in OAD, IAD, and IDC. m-MB in OAD were more correlated with that of IDC, whereas n-MEVs in OAD were more related to those in IAD. Thus, indoor bioaerosols can be affected by different source according to bioaerosol size. Additionally, risk of bioaerosols can be different according to dominant taxa, and therefore we suggested that further study for risk of dominant taxa according to environments is necessary. We suggested that nano-sized microbial EVs should be included as parameters to manage air quality.